About Academics, Pandemic, Confinement, and Work Logs: Experiences of Some University Students in the Context of COVID-19 - Palma Campos, Claudia (2020)
Historically, women have carried the burden on their shoulders of looking after their families, this has implicated an overload of household chores and their lack of equitable division has increased by the COVID-19 pandemic. In the university context, the research to make visible and analyze all social problems is not necessarily reversed to analyze the contexts of its female workers, ignoring the living conditions of those who belong to this entity of "social privileges". What can some university women say about this experience of confinement and family and work overload?